ANALISIS KELAYAKAN INVESTASI USAHA KECIL WARNET (Studi Pada Warnet Bulian City Net Muara Bulian) - Sumantri Sumantri (Ekonomis: Journal of Economics and Business, 2018)
Market Prospects At this time the need for information society is greatly improved, to meet this need required adequate facilities in order to send and receive good information, especially in telecommunication services. Warnet as a business that provides computer rental services to access the internet. Because the cafe business around Islamic High School is only 5 (five), then the researchers only do 1 sample. Assessments that have been done above with various methods of business feasibility study analysis then the business cafe "Bulian City Net" is feasible to run by looking at considerations of business feasibility study analysis method In full capital return is only required operational for 1 year 9 months 2 days, then the capital Rp.100.000.000 invested will return 100%. Net Cash Flow reach Rp 54.700.000 per peride per year then it is feasible to run Multy Game business. This Net. Because Net Present Value is positive, that is comparison between PV Process and PV investment.Keywords: Analysis, Investment, Business